Açaí Waste Biochar Combined with Phosphorus Fertiliser and Phosphorus Use Efficiency in Cowpea (Vigna unguiculata (L.) Walp) - Ana Rita de Oliveira Braga; Vinicius John; Criscian Kellen Amaro de Oliveira Danielli; Heiriane Martins Sousa; Filipe Eduardo Danielli; Cláudia Saramago de Carvalho Marques-dos-Santos; Danielle Monteiro de Oliveira; Newton Paulo de Souza Falcão (Agronomy)
Biochar is a multifunctional tool that enhances soil quality, with particularly positive effects on acidic soils with low nutrient content, common in tropical regions worldwide, such as in the Amazon region in Brazil. This study investigates the effects of açaí fruit waste biochar (Euterpe oleracea Mart.) amendment and phosphate fertilisation on the chemical characteristics of a Ferralsol and on the biological components of cowpea (Vigna unguiculata (L.) Walp). In a greenhouse setting, a randomised block design was employed, testing five doses of biochar (0, 7.5, 15, 30, and 60 t ha−1) combined with four doses of phosphorus (P) (0, 40, 80, and 120 kg ha−1), resulting in 20 treatments with three replicates and 60 experimental units. Cowpea responded to inorganic fertilisation, with lower doses of P limiting the biological components (height, leaves, leaf area, dry biomass, and dry root mass). Higher doses of biochar and P increased the soil’s available P content by up to 2.3 times, reflected in the P content of cowpea dry biomass. However, this increase in biochar and P levels led to a maximum increase of 7.7% in agronomic phosphorus efficiency (APE) in cowpea in the short term. The higher doses of biochar promoted increases in pH value, cation exchange capacity (CEC), and the contents of potassium (K), calcium (Ca), and total nitrogen (N). In contrast, a decrease in magnesium (Mg) and aluminium (Al) levels was observed, while the concentration of easily extractable glomalin (EE-GRSP) was not significantly affected during the evaluated period. We conclude that biochar altered the soil environment, promoting the increased solubility and availability of phosphorus.